Reflections on Body, Praxis and Corporeity (Research, Society and Development, 2019)
This essay aims to present some considerations about the relation praxis and corporeity, starting from the study of the body conceptions that marked the educational processes from the nineteenth century and the constitution of Physical Education as a disciplinary activity. In the historical-critical analysis of these discourses, pedagogical aspects stand out that, in the school-capital-work context, point to the overcoming of the machinic vision of the body through a transforming praxis and an active corporeity of the subject. Thus, the reflection proposed here intends to contribute to corporeal studies and constitutes the contribution of an ongoing research that investigates the approach of the body in the formation of professional technical courses.